Entrepreneurship : strategies and resources / Marc J. Dollinger. - Dollinger, Marc J. (Austen Press ; [Marketed and distributed by] Irwin, 1995)
Includes comprehensive case studies of: Quick-Dry Ball, Prolingua, Venture Capital Access, Inc., Roland and Associates, Fumero Artfabrics, Inc., PotatoQuick!, North Atlantic Loading Service, TV Answer (an interactive video data service), International Galvanizing Inc. (Marseilles, France), Bright Ideas, Rubio's Restaurants Inc., Suzy's Zoo, Windsor Industries, Inc., and Engineered Solutions, Inc., as well as many brief case studies.